If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x) = 2x + 1 x = 2x + 1 Reorder the terms: x = 1 + 2x Solving x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. x + -2x = 1 + 2x + -2x Combine like terms: x + -2x = -1x -1x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 -1x = 1 + 0 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 6x^2+(12-8a)x-16a=0 | | 30x+20=120 | | 7+12n= | | x=tln(2t)i | | (-42-4)-(-7-3)=y | | 8b^2-16b= | | 5y+9=3y-7 | | 7x-1o= | | 3y-7=5y+9 | | 15+(2-20)=y | | 3y-7=5y-9 | | 7x-10=24prove | | 6x+18=6xX+6-3 | | (3+9)-(-3+2)=y | | (-42+-4)+7+-3=y | | (-8+1)+4=y | | 1.5x+70=700 | | 8-(3+2)=t | | (-15-4)-(-2-15)=y | | q=3k+3 | | 525+.21x=585+.12x | | 3x+2=13(X+4) | | 3x+2=(x+4) | | y+9=2(x-1) | | y-8=-4(x+7) | | 3(0.9-1)-(x+0.6)=-0.2 | | x-5=20*10 | | 1/2x+3=1/3x+2 | | m=(2-1) | | w=4+15 | | 2(x-2)=2x-6 | | 2x-8x+4=x-9+13 |